2008
DOI: 10.1112/s1461157000000607
|View full text |Cite
|
Sign up to set email alerts
|

Computing with Nilpotent Orbits in Simple Lie Algebras of Exceptional Type

Abstract: Let G be a simple algebraic group over an algebraically closed field with Lie algebra g. Then the orbits of nilpotent elements of g under the adjoint action of G have been classified. We describe a simple algorithm for finding a representative of a nilpotent orbit. We use this to compute lists of representatives of these orbits for the Lie algebras of exceptional type. Then we give two applications. The first one concerns settling a conjecture by Elashvili on the index of centralizers of nilpotent orbits, for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
101
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(105 citation statements)
references
References 4 publications
4
101
0
Order By: Relevance
“…In the remaining types and (ultimately for all truncated biparabolics, we found upper and lower bounds [10,Sects. 5,6] and [16, 6.7]) on ch Y (g x β ) which imply via [10, 7.1] that GK dim Y (g x β ) = rk g. Again, by the general theory developed already in [13,Sect. 4], it follows that Y (g x β ) is polynomial up to localization by x β .…”
Section: 5mentioning
confidence: 96%
See 1 more Smart Citation
“…In the remaining types and (ultimately for all truncated biparabolics, we found upper and lower bounds [10,Sects. 5,6] and [16, 6.7]) on ch Y (g x β ) which imply via [10, 7.1] that GK dim Y (g x β ) = rk g. Again, by the general theory developed already in [13,Sect. 4], it follows that Y (g x β ) is polynomial up to localization by x β .…”
Section: 5mentioning
confidence: 96%
“…Elashvili had asked if index g x = rk g. The Vinberg inequality implies that index g x rk g. The question of equality easily reduces via Jordan decomposition to the nilpotent case. Following this, Yakimova [32] has shown that equality holds for g classical and the remaining cases have been checked by de Graaf using computer aided calculations [6]. It is now even known that Y (g x ) is polynomial, for example, by Brown and Brundan [4] in type A and in types A and C by Panyushev, Premet and Yakimova [28].…”
Section: 2mentioning
confidence: 99%
“…Remark 2. In view of the now established truth of the Elashvili conjecture ( [39], [11]), (ii) also follows from [31,Cor. 2.3] (see also [19, 3.1, Remarks]), where in addition both sides equal rank g. However it can be useful to have an independent proof.…”
Section: Lemmamentioning
confidence: 99%
“…In this sense our approach stresses the relationship between nilpotent orbits in g and those in the ambient gl n (k). We also note that in [2] De Graaf presents a probabilistic 'trial and error' algorithm for computing representatives of nilpotent orbits over any algebraically closed field. Whilst the parameters may be set so as to deliver arbitrarily large probability of success, the representative obtained is not canonical.…”
Section: Introductionmentioning
confidence: 99%